(untitled) (Applied Biological Research, 2016)
The present investigation was carried out to study the gas exchange parameters in backcross inbred lines of ‘Improved White Ponni’ (IWP) introgressed with different drought yield QTLs and their parents raised under control and stress conditions. Various gas exchange parameters and single plant yield were observed using portable photosynthetic system (infra red gas analyser - IRGA). Among the genotypes, three combination of QTL line IWP-4-2 recorded significantly higher photosynthetic rate (22.97 μ mol CO2 m-2 s-1), stomatal conductance (0.36 mol H2O m-2 s-1), transpiration rate (6.25 mmol H2O m-2 s-1), internal CO2 concentration (240.82) ratio between internal and atmospheric CO2 concentration (0.25) and single plant yield (15.11) which was on par with the tolerant parent Apo (an high yielding indica cultivar moderately tolerant to drought stress) under severe moisture stress regime. Overall study clearly revealed that, the performance of introgressed line with three drought QTLs (IWP-4-2) was better than two drought QTL introgressed lines of IWP-1-52 and IWP-1-57. Results from graphical genotyping using three foreground and 36 polymorphic background markers revealed that, the three QTL introgressed line IWP-4-2 had 72.20% genome recovery from Improved White Ponni, 13.89% from APO and 13.89% heterozygous region.